Chronic Pulmonary Aspergillosis Complicating Bronchial Atresia - Mazen O. Al-Qadi; Dereddi Raja S. Reddy; Brandon T. Larsen; Vivek N. Iyer (Case Reports in Medicine)
Bronchial atresia is a rare pulmonary developmental anomaly characterized by the presence of a focal obliteration of a segmental or lobar bronchial lumen. The lung distal to the atretic bronchus is typically emphysematous along with the presence of mucus filled ectatic bronchi (mucoceles). BA is usually asymptomatic but pulmonary infections can rarely develop in the emphysematous lung distal to the atretic bronchus. We present a unique case of chronic pulmonary aspergillosis (CPA) in a patient with BA with no evidence of immune dysfunction. The patient was treated initially with voriconazole and subsequently underwent surgical excision of the involved area. On follow-up, she has done extremely well with no evidence for recurrence. In summary, we describe the first case of chronic pulmonary aspergillosis in an immunocompetent patient with bronchial atresia.